Review on Perioperative and Oncological Outcomes of Robotic Gastrectomy for Cancer - Giuliani, Giuseppe (J Pers Med, 2021)
Background. Minimally invasive gastrectomy is currently considered a valid option to treat gastric cancer and is gaining increasing acceptance. Recent reports have suggested that the application of robots may confer some advantages over conventional laparoscopy, but the role of robotic surgery in clinical practice is still uncertain. We aimed to critically review the relevant evidence comparing robotic to standard laparoscopic surgery in performing radical gastrectomy. Methods. The Pubmed/Medline electronic databases were searched through February 2021. Paper conference and the English language was the only restriction applied to our search strategy. Results. According to the existing data, robotic gastrectomy seems to provide some benefits in terms of blood loss, rate of conversion, procedure-specific postoperative morbidity, and length of hospital stay. Robotic gastrectomy is also associated with a longer duration of surgery and a higher economic burden as compared to its laparoscopic counterpart. No significant differences have been disclosed in terms of long-term survivals, while the number of lymph nodes retrieved with robotic gastrectomy is generally higher than that of laparoscopy. Conclusions. The current literature suggests that robotic radical gastrectomy appears as competent as the conventional laparoscopic procedure and may provide some clinical advantages. However, due to the relative paucity of high-level evidence, it is not possible to draw definitive conclusions.